2007
DOI: 10.1038/sj.ejcn.1602907
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns associated with vitamin/mineral supplement use and smoking among women of the E3N–EPIC cohort

Abstract: Background/Objectives: An understanding of the relationships between dietary habits and supplement use or smoking is useful for aetiological studies and surveillance purposes. The objective of this study is to describe dietary patterns associated with vitamin/mineral supplement use and smoking habits in French women. Methods: Scores for dietary patterns were obtained by factor analysis in 64 252 women from the French E3N-EPIC cohort. The association with supplement and tobacco use was investigated by logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 46 publications
2
32
0
Order By: Relevance
“…The Multiethnic Cohort Study found that physical activity ($3 times/week) was positively asso- (14) . In addition, participants with the healthy pattern have been reported to have higher physical activity levels and to be more likely to take dietary supplements daily (27) (33) .…”
Section: Discussionmentioning
confidence: 99%
“…The Multiethnic Cohort Study found that physical activity ($3 times/week) was positively asso- (14) . In addition, participants with the healthy pattern have been reported to have higher physical activity levels and to be more likely to take dietary supplements daily (27) (33) .…”
Section: Discussionmentioning
confidence: 99%
“…The Epidemiological Prospective Study in Cancer (EPIC) has reported dietary patterns in adults and elderly individuals in 10 European countries (Bamia et al, 2007;Masala et al, 2007;Touvier et al, 2009) using locally designed FFQs. Comparisons of dietary patterns were usually studied with a single 24-h recall questionnaire, standardised for all participant countries.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been reported that supplement use is more frequent in women than in men (1,11,12) , in older people than in younger people (1,12) and in people with higher levels of education compared with those with lower levels of education (13,14) . Supplement users tend to be more physically active (15,16) , less likely to smoke (7,15) , have a lower BMI (11,14) and to make a healthier food choice (1,17,18) than non-users. However, little attention has been given to heterogeneity among supplement users.…”
mentioning
confidence: 99%